Introduction - Silva, Guilherme de Aquino (Romanitas - Revista de Estudos Grecolatinos, 2025)
Introduction of the dossier: "Processes of expansion and integration in the ancient Mediterranean".
Keywords: Expansion; Integration; Mediterranean